Wadah SIG EMiBio-EMiBio: Agriculture Meets Technology / Dr Muhammad Aidil Ibrahim... [et al.] - Ibrahim, Dr Muhammad Aidil; Azmir, Dr Izzati Adilah; Ahmad Mazian, Dr Mu’adz; Mohd Noh, Dr Hisham; Sharif, Amirah; Baharin, Dr Siti Nor Atika; Maadon, Siti Nursyazwani (UiTM Cawangan Negeri Sembilan, 2022)
EMiBio is one of the most prominent and active Special Interest Group (SIG) of UiTM Cawangan Negeri Sembilan. Their primary aim is to empower modern agriculture by associating modern technologies that can enhance agricultural qualities. In achieving their aim, they have strategized on conducting effective research, promoting research collaborations, public knowledge sharing, and organizing seminars in propagating modern agricultural ideologies. The specific research interest area is being portrayed in the EMiBio acronym, “Environmental MIcroBIOlogy”. EMiBio is focusing on the association of microbiology technology in intensifying environmental sustainability. The official EMiBio’s logo portrays a visualization of the deoxynucleic acid (DNA) as the core structure of a colorful tree. The multiple colors concept was to represent the multidisciplined research backgrounds of the dedicated research members behind EMiBio, all united to realizing the aim of the group.